Differences in F-Wave Characteristics between Spinobulbar Muscular Atrophy and Amyotrophic Lateral Sclerosis - Fang, Jia; Cui, Liying; Liu, Mingsheng; Guan, Yuzhou; Li, Xiaoguang; Li, Dawei; Cui, Bo; Shen, Dongchao; Ding, Qingyun (Frontiers in Aging Neuroscience, 2016)
There is limited data on the differences in F-wave characteristics between spinobulbar muscular atrophy (SBMA) and lower motor neuron dominant (LMND) amyotrophic lateral sclerosis (ALS). We compared the parameters of F-waves recorded bilaterally from the median, ulnar, tibial, and deep peroneal nerves in 32 SBMA patients, 37 patients with LMND ALS, and 30 normal controls. The maximum F-wave amplitudes, frequencies of giant F-waves, and frequencies of patients with giant F-waves in all nerves examined were significantly higher in the SBMA patients than in the ALS patients and the normal controls. The mean F-wave amplitude, maximum F-wave amplitude, frequency of giant F-waves, and frequency of patients with giant F-waves in the median and deep peroneal nerves were comparable between the ALS patients and normal controls. Giant F-waves were detected in multiple nerves and were often symmetrical in the SBMA patients compared with the ALS patients. The number of nerves with giant F-waves seems to be the most robust variable for differentiation of SBMA from ALS, with an area under the curve of 0.908 (95% CI: 0.835–0.982). A cut-off value of the number of nerves with giant F-waves (≥ 3) for diagnosing SBMA showed high sensitivity and specificity: 85% sensitivity and 81% specificity vs. ALS patients. No significant correlations were found between the pooled frequency of giant F-waves and disease duration in the SBMA (r = 0.162, P = 0.418) or ALS groups (r = 0.107, P = 0.529). Our findings suggested that F-waves might be used to discriminate SBMA from ALS, even at early stages of disease.